Crowdfunding for inter-faith peace: youth, networked social movement, and muslim philanthropy NGOs in contemporary Indonesia - Anoraga, Bhirawa (IAIN Salatiga, 2023)
This study examines the involvement of Indonesian youth and Muslimphilanthropy NGOs in the promotion of inter-faith harmony throughcrowdfunding. Crowdfunding or online fundraising has been rapidly growing inIndonesia. It has been used to respond to various issues, among which is religiousviolence. Oftentimes, when radical acts happened in Indonesia, people turnedto crowdfunding to express inter-faith solidarity and support. This study drawsfrom the concept of networked social movement to explain the characteristicsof crowdfunding campaigns for inter-faith harmony. This concept highlightscontemporary online movements that are spontaneous, leaderless, and temporalin nature which is distinct from the well-organized movements commonly studiedby scholars. This study employs digital ethnography on campaigns that respondedto religious violence in the largest crowdfunding platform in Indonesia, Kitabisa,which is complemented by interviews with the campaign initiators and Muslimphilanthropy NGOs. This article argues that the characteristics of network social movement fit with the current youth generation that is assumed to be sociallyapathetic and more immersed in developing themselves and consuming media.Nevertheless, despite the spontaneous and temporal tenets, the youth’s inter-faithmovements were able to mobilize a significant number of donations and attractMuslim NGOs that were often perceived to be sectarian to support the inter-faithcampaigns. The findings of this study contribute to the studies on Indonesianyouth, Islamic philanthropy, and the state of inter-faith relations in Indonesia,which was argued to be experiencing a conservative turn.